Improving Nutritional Intake During Pregnancy Through Targeted Nutrition Education: A Quasi-Experimental Study: The Effect of Providing Nutrition Education on Increasing Nutritional Intake in Pregnant Women - Suriati, Israini; Juliani, Reski (Journal of Applied Nursing and Health, 2025)
Background: Adequate nutritional intake during pregnancy is essential to support maternal health and fetal development. One of the main factors contributing to poor nutritional status among pregnant women is the lack of knowledge and understanding of balanced nutrition. Nutrition education serves as a key strategy to improve nutritional literacy and promote healthier dietary behaviors throughout pregnancy. This research aims to examine the effect of nutrition education on improving the nutritional intake of pregnant women. Methods: This quantitative study used a quasi-experimental pre-test and posttest design without a control group. A total of 50 pregnant women in their second and third trimesters were recruited through purposive sampling from Wara Selatan Health Center, Palopo City, Indonesia. Inclusion criteria were willingness to participate and no chronic diseases. The intervention consisted of three structured education sessions over two weeks, each lasting 45 to 60 minutes, delivered by trained health workers using visual aids and interactive discussions. Data were collected using a validated nutritional knowledge questionnaire and a 24-hour dietary recall form (α = 0.81; r = 0.84). Data analysis was performed using a paired t-test via SPSS version 26 with a significance level of p < 0.05 Results: Research has shown that a significant increase in mean nutrient intake after the intervention: carbohydrates from 180 ± 45 g to 210 ± 50 g, protein from 60 ± 12 g to 80 ± 16 g, iron from 18 ± 6 mg to 24 ± 8 mg, vitamin A from 700 ± 200 mcg to 950 ± 250 mcg, and calcium from 800 ± 180 mg to 1000 ± 200 mg. Research has shown that p-values < 0.05, indicating statistically significant improvements after nutrition education. Conclusion: This study shows that structured nutrition education can increase the intake of carbohydrates, protein, iron, vitamin A, and calcium in pregnant women. These findings support the importance of nutrition education as part of antenatal care. Practically, this intervention can be integrated into routine programs at Puskesmas and Posyandu through pregnancy classes and direct counseling by midwives or cadres. Simple and locally appropriate education has proven effective and can be widely applied, especially in primary health facilities.